Alumina‐Epoxy‐Pore Composites Fabricated by Inkjet Printing for Wireless Communication Technology - Seongguk Jeong; Kwangho Park; Myoung Pyo Chun; Jong Hee Kim; Dae Ho Yoon; Youngje Sung (Advanced Materials Interfaces, 2024)
Abstract Reducing transmission loss via composites with pores has emerged as a breakthrough method for information and communications technology applications. The super/extremely high‐frequency signals used in the technologies result in significant transmission loss. Demand for low‐loss materials with low dielectric constant (Dk) and low dissipation factor (Df) has increased in recent years. Here, it is demonstrated that the pore in composites can be reduced Dk and Df of composites with pores (air). In fabrication of composites, a drop‐on‐demand (DOD) inkjet printing method to fabricate composites with pores (air) for use in wireless communications technologies. The DOD method is a simple but versatile manufacturing process at low cost. Its versatile process makes it possible to control the amount of resin and pore in fabrication of the composites and moreover to distribute all their components isotopically and homogeneously. It is possible to fabricate the composites with a lower Dk and Df value by increasing pore amount in the composites. This strategy enabled us to inexpensively manufacture dielectric substrates with low Dk and Df values, greatly contributing to the communications technology industry.